1995
DOI: 10.1002/ajim.4700270606
|View full text |Cite
|
Sign up to set email alerts
|

United states non‐Hodgkin's lymphoma surveillance by occupation 1984‐1989: A twenty‐four state death certificate study

Abstract: Death certificates from 23,890 male and female non-Hodgkin's lymphoma (NHL) cases and 119,450 noncancer controls from 24 states for the period 1984-1989 were used to generate hypotheses regarding occupational associations. Cases were frequency matched by age, race, and gender with five controls per case. Odds ratios were calculated for 231 industries and 509 occupations. Significant associations were observed for a variety of white-collar professionals (i.e., real estate agents, secretaries, bookkeepers, teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 57 publications
(23 reference statements)
0
28
3
Order By: Relevance
“…The findings from the case-control studies (54)(55)(56)(78)(79)(80)83,84) shown in Table 12 add further support for an association between solvents, specifically TCE, and nonHodgkin's lymphoma. Six of seven studies showed elevated ORs, two were statistically significant, and several reported TCE (rather than general solvent) exposure.…”
Section: Community-based Studiesmentioning
confidence: 77%
“…The findings from the case-control studies (54)(55)(56)(78)(79)(80)83,84) shown in Table 12 add further support for an association between solvents, specifically TCE, and nonHodgkin's lymphoma. Six of seven studies showed elevated ORs, two were statistically significant, and several reported TCE (rather than general solvent) exposure.…”
Section: Community-based Studiesmentioning
confidence: 77%
“…Significantly increased risks of NHL among welders have been reported in some case-control studies (OR range: 1.4-3.6), 34 260 reported that NHL death was associated positively with employment as an elementary school teacher among both blacks (OR among females 5 1.8, 95% CI: 1.1-2.9) and whites (OR among females 5 1.4, 95% CI: 1.2-1.5; OR among males 5 1.6, 95% CI: 1.3-2.0) across the 4 geographic regions of the US. Findings from a meta-analysis of 14 studies (RR range: 0.31-3.60) indicated a significantly elevated relative risk of NHL among schoolteachers (meta-RR 5 1.36, 95% CI: 1.13-1.62); however, the authors suggested that results may have been affected by publication bias.…”
Section: Occupational and Environmental Chemical Exposurementioning
confidence: 85%
“…263,270,271 A nonsignificant positive association was found among male bookbinders, printers, photoengravers and typesetters (SIR 5 2.24, 95% CI: 0.96-4.41). 272 Other occupational groups for which nonsignificant findings have been reported include synthetic abrasive product workers, 273 266,295 Several case-control studies have found significant associations of NHL risk with various occupational categories, including chemical manufacturing maintenance subgroups, 236 cigarette factory workers, 296 electrical fitters, 297 rail and road transport workers, 266 accountants, 266 secretaries, 266 photographic lab workers, 266 carpenters, 21,214 managerial and professional workers 176,260 and printing workers. 34,298 These studies are uninformative as a lack of individual exposure information in many of these studies precludes exposure-specific interpretations.…”
Section: Occupational and Environmental Chemical Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…In an analysis which overlapped with that already described, men and women who died from non-Hodgkin's lymphoma in the same 24 states in the United States during 1984-1989 were identified from death certificates and compared with referents (5 per case, frequency matched for age, gender and race) who died of causes other than cancer (21). Information about each subject's occupation was obtained from his or her death certificate, and MOR values were calculated for specified occupations in comparison with all other occupations combined by logistic regression.…”
Section: Mortality From Non-hodgkin's Lymphoma By Occupation In 24 Stmentioning
confidence: 99%